2022
DOI: 10.1039/d1ea00102g
|View full text |Cite
|
Sign up to set email alerts
|

Terrestrial carbon cycle: tipping edge of climate change between the atmosphere and biosphere ecosystems

Abstract: Being the tendency to couple with multiple elements, Carbon forms the most complex molecules, which is the basic chemistry of all life forms. As our climate system is inextricably coupled...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 199 publications
1
3
0
Order By: Relevance
“…As depicted in Fig. 4b, the Ni-PCNF electrocatalysts achieved a FE CO in excess of 80% across potential ranges of −0.8 to −1.3 V RHE , peaking at 94% at −1.0 V RHE, and no liquid products were detected by 1 H nuclear magnetic resonance ( 1 H NMR) post a 1 hour electrolysis, as per the results presented in Fig. S10.…”
Section: Resultssupporting
confidence: 66%
See 1 more Smart Citation
“…As depicted in Fig. 4b, the Ni-PCNF electrocatalysts achieved a FE CO in excess of 80% across potential ranges of −0.8 to −1.3 V RHE , peaking at 94% at −1.0 V RHE, and no liquid products were detected by 1 H nuclear magnetic resonance ( 1 H NMR) post a 1 hour electrolysis, as per the results presented in Fig. S10.…”
Section: Resultssupporting
confidence: 66%
“…The unrelenting escalation of atmospheric CO 2 concentrations continues to herald a multitude of global environmental challenges. 1 The electrochemical CO 2 reduction reaction technique, which can transform CO 2 into a range of valuable chemicals and fuels, has emerged at the forefront of these endeavors, presenting a visionary paradigm for the valorization of this otherwise deleterious greenhouse gas. 2 A diverse array of reduction products can be obtained with distinct implications for energy and industrial applications in CO 2 RR procedure such as CO, CH 4 , CH 3 COO − , and C 2 H 4 .…”
Section: Introductionmentioning
confidence: 99%
“…This would consider the magnitude and direction of changes in PNPP, ANPP and HNPP, as well as the synergistic or antagonistic effects among the different influencing factors. Finally, various new methods based on machine learning were recently applied to such research, and these methods were demonstrated to be superior to our method in some aspects [51,52]. Anyway, our method is still the most extensively used approach at present for quantifying the impacts of anthropogenic activities and climatic change, due to the relatively simple operation and the easier data acquisition [19].…”
Section: Methodological Considerations and Limitationsmentioning
confidence: 85%
“…Soil organic carbon (SOC) is a key component of the global carbon cycle [1][2][3] and stores more carbon than the atmosphere and biosphere combined [4]. Soil organic carbon (SOC) is not only composed of plant residues and animal wastes, but also includes organic matter that has been transformed by a diverse array of soil microorganisms, such as fungi and bacteria.…”
Section: Introductionmentioning
confidence: 99%